Assessing the effectiveness of the adaptation learning model for dyslexic students’ engagement: a quasi-experimental study - Hamid, Siti Suhaila Abdul; Admodisastro, Novia; Ismail, Zahian; Radzuan, Nabilah Filzah Mohd; Kamaluddin, Adzhar; Mahmud, Murni (Institute of Advanced Engineering and Science, 2025)
Students with dyslexia require individual learning approaches due todifferent mastery and engagement levels. The conventional approach couldnot adjust the learning style automatically and burdened the teacher,especially in bigger class sizes. We proposed an adaptive learning model forstudents with dyslexia (ALMo-DML) that personalized the learning basedon the mastery level and behavior. ALMo-DML can retain the studentslonger using adaptive elements. This paper examines the effectiveness of theALMo-DML prototype in increasing student engagement by comparing itwith MyLexic, non-adaptive learning using a quasi-experiment. Theparameters involve on-task/off-task behavior, time spent, and usability test.Descriptive statistics, hypothesis testing, software usability scale (SUS), andobservation forms were used to measure the engagement parameters. Theresult shows a longer on-task time with an average of 22 minutes when usingthe ALMo-DML prototype compared to the non-adaptive application withonly 12 minutes (p-value<0.05) using the Mann-Whitney U test. Besides,observation data support the finding indicating engagement from gestures,keyboard, and mouse clicks. This study proved that ALMo-DML showed apositive effect on the engagement of students with dyslexia compared withnon-adaptive learning. Hence, ALMo-DML is highly recommended as asupporting material in helping students with dyslexia.